2009
DOI: 10.1089/jwh.2008.1193
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Gender in Chronic Lyme Disease

Abstract: Patients with chronic Lyme disease differ with regard to gender from those with either B. burgdorferi infection or post-Lyme disease syndrome. This finding suggests that illnesses with a female preponderance, such as fibromyalgia, chronic fatigue syndrome, or depression, may be misdiagnosed as chronic Lyme disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 23 publications
3
12
0
1
Order By: Relevance
“…While CLD and PTLDS share many similarities in the subjective symptoms of fatigue, pain, neurocognitive dysfunction, and others, patients often seek care for or are given the diagnostic label of CLD when current or past evidence of Borrelia infection cannot be determined. A review of antibiotic treatment studies for CLD found female to male ratios which ranged from 1.8 to 2.8 (Wormser and Shapiro 2009). Similarly, in our retrospective chart review of patients, we found that women represented 66 % of patients with medically unexplained symptoms that could not be given a diagnosis using current CDC and IDSA guidelines for early Lyme disease, late Lyme disease, or PTLDS (Aucott et al 2012).…”
Section: Chronic Lyme Diseasesupporting
confidence: 57%
See 2 more Smart Citations
“…While CLD and PTLDS share many similarities in the subjective symptoms of fatigue, pain, neurocognitive dysfunction, and others, patients often seek care for or are given the diagnostic label of CLD when current or past evidence of Borrelia infection cannot be determined. A review of antibiotic treatment studies for CLD found female to male ratios which ranged from 1.8 to 2.8 (Wormser and Shapiro 2009). Similarly, in our retrospective chart review of patients, we found that women represented 66 % of patients with medically unexplained symptoms that could not be given a diagnosis using current CDC and IDSA guidelines for early Lyme disease, late Lyme disease, or PTLDS (Aucott et al 2012).…”
Section: Chronic Lyme Diseasesupporting
confidence: 57%
“…Several publications have asserted that the female predominance in CLD is a result of misdiagnosed fibromyalgia, chronic fatigue syndrome, or depression, all conditions with similarly high female to male ratios (Sigal 1990;Hsu et al 1993;Wormser and Shapiro 2009). There is considerable symptom overlap between CLD, PTLDS, and these other symptom-based syndromes, and it remains difficult if not impossible to separate them clinically.…”
Section: Chronic Lyme Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In the United States there is a male predominance of cases [2], [3]. This is not necessarily true in Europe where in some countries such as Germany there is a female predominance [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…The reference cited to support this claim (12) actually shows that there is an equal gender distribution among patients diagnosed with PLDS. Also, the reference cited by Stricker and Winger (5) to support the claim that patients in their study (10) had a gender distribution consistent with CLD has no relevance to CLD whatsoever since it addresses a completely different issue in Lyme disease (reinfection).…”
Section: Authors' Replymentioning
confidence: 97%